The Implementation of Regional Regulation of Gorontalo City Number 17 Of 2011 Concerning The Retribution of Market Services in Gorontalo City - Sri Yulianty Mozin; Ainun Fauzia Idrus; Sintia Anwar (International Interdisciplinary Conference on Sustainable Development Goals, 2021)
The aims of this study are to analyze the implementation of regional regulation of Gorontalo City Number 17 of 2011 concerning The Retribution of Market Services in Gorontalo City, and the factors that determine the implementation of the Regional Regulation. The research method used is descriptive qualitative. Data collection techniques through interviews, observation and documentation. Data analysis techniques through data reduction, data display and conclusion. The results showed that the implementation of Gorontalo City Regional Regulation Number 17 of 2011 concerning Retribution of Market Services in Gorontalo City was carried out through a systematic strategy based on planning, implementing and monitoring that was carried out was not as expected. The inhibiting factors for the implementation of Regional Regulations are the number of human resource retributors who are not in accordance with the volume of work required, the utilization of accounting information systems that are not yet integrated, and the attitude of retributors and traders who are not enthusiastic in supporting the implementation process. The supporting factors for the implementation of Regional Regulations are effective communication between policy implementers and bureaucratic structures supported by clear SOPs and short fregmentation in the distribution of responsibilities.